Pesticide Profiles Toxicity, Environmental Impact, and Fate - Kamrin, Michael A. (CRC Press, 2009)
Pesticide Profiles: Toxicity, Environmental Impact, and Fate is like three books in one-it is a profile containing specific information about 137 pesticides, a primer of environmental toxicology, and an extensive trade name index. Profiles of each pesticide contain regulatory information, toxicity assessments, environmental fate data, physical properties, and acceptable exposure limit values. What these values and data mean in terms of human toxicity is clearly interpreted as well.